Apakah Efek Media Sosial dalam Aktivitas Perdagangan Saham di Indonesia Berlaku pada Jenis Saham? Systematic Literature Review - Risti Herliana; Nugroho Wisnu Murti; Indriyana Widyastuti (STIE AUB Surakarta, 2026)
This study synthesizes empirical evidence on the relationship between social media and stock trading activity in Indonesia, examining whether the effect applies uniformly across all stocks or varies by stock characteristics. A Systematic Literature Review (SLR) was conducted using Publish or Perish on Google Scholar with the keywords